CHO cell production and sequence improvement in the 13C6FR1 anti-Ebola antibody. Issue 2 (17th February 2016) - Pettit, Dean K.; Rogers, Richard S.; Arthur, Kelly; Brodsky, Yan; Clark, Rutilio H.; Crowell, Chris; Ennis, Jane; Gillespie, Alison; Gillespie, Ron; Livingston, Brittney; Nalbandian, Edith; Pace, Danielle; et al.
ABSTRACT: From March 2014 through February 2015, the Ebola virus spread rapidly in West Africa, resulting in almost 30, 000 infections and approximately 10, 000 deaths. With no approved therapeutic options available, an experimental antibody cocktail known as ZMapp™ was administered to patients on a limited compassionate-use basis. The supply of ZMapp™ was highly constrained at the time because it was in preclinical development and a novel production system (tobacco plants) was being used for manufacturing. To increase the production of ZMapp™ for an uncertain future demand, a consortium was formed in the fall of 2014 to quickly manufacture these anti-Ebola antibodies in Chinese hamster ovary (CHO) cells using bioreactors for production at a scale appropriate for thousands of doses. As a result of the efforts of this consortium, valuable lessons were learned about the processing of the antibodies in a CHO-based system. One of the ZMapp™ cocktail antibodies, known as c13C6FR1, had been sequence-optimized in the framework region for production in tobacco and engineered as a chimeric antibody. When transfected into CHO cells with the unaltered sequence, 13C6FR1 was difficult to process. This report describes efforts to produce 13C6FR1 and the parental murine hybridoma sequence, 13C6mu, in CHO cells, and provides evidence for the insertion of a highly conserved framework amino acid that improved the physical properties necessary for high-level expression and purification. Furthermore, it describes the technical and logistical lessons learned that may be beneficial in the event of a future Ebola virus or other pandemic viral outbreaks where mAbs are considered potential therapeutics.